Praca naukowa to wydanie umysłu na ciągły niedosyt. Listy Stefanii Skwarczyńskiej do Czesława Zgorzelskiego - Gomóła, Anna (Zagadnienia Rodzajów Literackich, 2019)
In the Library of the Catholic University of Lublin fifty seven letters and correspondence cards which Stefania Skwarczyńska sent to Czesław Zgorzelski between the years 1948–1984 are kept. They are a trace of professional contacts between scholars — documenting in an aspectual way Polish scientific life. Letters, although in a private form, concern professional matters, such as: organisation of the research institution, politics concerning employment, education of young scholars, taking part in conferences, publishing scientific works as well as their circulation. A vast part of them is dedicated to the history of establishing “Zagadnienia Rodzajów Literackich” [“The Problems of Literary Genres”].